Capital importers pay more for their imports - Antonis Adam; Thomas Moutos (Center for Economic Studies and ifo Institute (CESifo), 2012)
We examine the effects that a country's net capital flows have on the (border) prices that a country pays for its imports of goods. Using data from 2000 to 2009 for 11 euro area countries we utilize a pricing-to-market specification to study exporters' pricing behavior to the rest of the countries in the sample, at the industry level, for 900 goods disseminated at the 4- digit Standard International Trade Classification (SITC- revision 3) level. This allows us to construct a panel dataset which contains observations across exporters, importers, industries and time, ending up with a total of 594,327 observations. We find a strong influence of the importing country's net capital inflows on the border prices of its imports of goods. This result is robust across different specifications of the underlying model, as well to different sample disaggregations across types of capital flows, product categories, and exporters.
Keywords: F32; F34; F36; 330; capital flows; import prices; pricing to market; globalization; euro area; Kapitalimport; Import; Außenhandelspreis; Globalisierung; Schätzung; Eurozone